Low-input CUT&Tag for efficient epigenomic profiling of zebrafish stage I oocytes - Zheng, Qianwen; Wu, Xiaotong; Li, Xin; Mo, Xianming; Xiang, Bo; Chen, Jing (Frontiers in Cell and Developmental Biology, 2024)
Histone modification signatures mark sites of transcriptional regulatory elements and regions of gene activation and repression. These sites vary among cell types and undergo dynamic changes during development and in diseases. Oocytes produce numerous maternal factors essential for early embryonic development, which are significantly influenced by epigenetic modifications. The profiling of epigenetic modifications during oogenesis remains uniquely challenging due to the presence of numerous tightly wrapped granulosa cells. Here, we successfully established a low-input CUT&Tag (Cleavage Under Targets and Tagmentation) method tailored for zebrafish stage I oocytes. This advanced technique enables high-resolution profiling of histone modifications and DNA-binding proteins, critical for understanding chromatin dynamics in developing oocytes. In this study, we detailed the workflow for this technique, including the isolation of pure stage I oocytes without somatic cells, library construction and quality monitoring. Our results demonstrate the method’s efficacy by identifying distinct histone modification patterns and analyzing differentially expressed genes in oocytes with and without granulosa cells. We also successfully profiled divergent histone modifications in oocytes derived from wild-type and huluwa mutants. These advancements overcome technical challenges in epigenetic research on zebrafish oocytes and establish a solid foundation for exploring the epigenetic regulatory mechanisms of maternal contribution.